Applying a Social Exclusion Framework to Explore the Relationship Between Sudden Unexpected Deaths in Infancy (SUDI) and Social Vulnerability - Shipstone, Rebecca A.; Young, Jeanine; Kearney, Lauren; Thompson, John M. D. (Frontiers in Public Health, 2020)
Background: Sudden Unexpected Death in Infancy (SUDI) is a leading cause of preventable infant mortality and strongly associated with social adversity. While this has been noted over many decades, most previous studies have used single economic markers in social disadvantage analyses. To date there have been no previous attempts to analyse the cumulative effect of multiple adversities in combination on SUDI risk. Methods: Based on sociological theories of social exclusion, a multidimensional framework capable of producing an overall measure of family-level social vulnerability was developed, accounting for both increasing disadvantage with increasing prevalence among family members and effect of family structures. This framework was applied retrospectively to all cases of SUDI that occurred in Queensland between 2010 and 2014. Additionally, an exploratory factor analysis was performed to investigate whether differing ‘types’ of vulnerability could be identified. Results: Increased family vulnerability was associated with four major known risk factors for sudden infant death: smoking, surface sharing, not-breastfeeding and use of excess bedding. However, families with lower levels of social vulnerability were more likely to display two major risk factors: prone infant sleep position and not room-sharing. There was a significant positive relationship between family vulnerability and the cumulative total of risk factors. Exploratory factor analysis identified three distinct vulnerability types (chaotic lifestyle, socioeconomic and psychosocial); the first two were associated with presence of major SUDI risk factors. Indigenous infants had significantly higher family vulnerability scores than non-Indigenous families. Conclusion: A multidimensional measure that captures adversity across a range of indicators highlights the need for proportionate universalism to reduce the stalled rates of sudden infant death. In addition to information campaigns continuing to promote the importance of the back-sleeping position and close infant-caregiver proximity, socially vulnerable families should be a priority population for individually tailored or community based multi-model approaches.